PENGARUH PEMBELAJARAN BERBASIS LINGKUNGAN TERHADAP SIKAP PEDULI LINGKUNGAN DAN KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN IPA - Perayanti Sinaga, Dian; Piliang, FennyMustika; Aldino, Jihan (Jurnal Metabio, 2024)
This research aims to explore the effectiveness of environmentally based learning in improving students' environmental care attitudes and science process skills. The research method used is a quantitative approach with a quasi-experimental design. The research subjects consisted of middle school students who were divided into a control group with a sample size of N=30 and an experimental group with a sample size of N=30. The experimental group received environment-based learning, while the control group received conventional learning. Data was collected through environmental care attitude questionnaires and science process skills tests using observation sheets, which were analyzed using descriptive and inferential statistical techniques. The research results show that environment-based learning significantly increases environmental care attitudes in accordance with the results of hypothesis testing with a smaller significance value of  = 0.05 (0.000 < 0.05) with df = 29. The research results show that environment-based learning significantly increases improve science process skills. according to research results with a smaller significance value of  = 0.05 (0.000 < 0.05) with df = 29. Students involved in environmental-based learning show increased understanding of environmental issues, motivation to participate in activities environmental conservation, as well as the ability to observe, classify and interpret scientific data. The implications of this research emphasize the importance of integrating environment-based learning in the education curriculum, as an effort to grow a generation that cares more about the environment and has adequate science process skills.